Impact of a Nurse Navigator Program on Referral Rates and Use of Fertility Preservation Among Female Cancer Patients: A 14‐Year Retrospective Cohort Study - Mackenzie Naert; Kimia Sorouri; Andrea Lanes; Abigail M. Kempf; Lucy Chen; Randi Goldman; Ann H. Partridge; Elizabeth Ginsburg; Serene S. Srouji; Zachary Walker (Cancer Medicine, 2025)
ABSTRACT Introduction Given the known detrimental impact of cancer treatment on fertility, fertility preservation (FP) is recommended for reproductive age patients who are newly diagnosed with cancer. However, the rate of referral to fertility specialists remains suboptimal. The objective of this study was to determine the impact of a dedicated Nurse Navigator Program (NNP) on the rate of referrals and utilization of FP services. Methods A retrospective cohort study of all women ≥ 18 years old referred for FP consultation with a known cancer diagnosis from 2007 to 2021 at a single, large academic center was conducted. FP referrals for non‐cancer indications were excluded. Descriptive statistics were performed including comparing referrals received per 30 days and FP utilization rates pre‐NNP (October 2007–September 2013) to post‐NNP (October 2013–December 2021). Results A total of 176 patients were included pre‐NNP and 990 patients post‐NNP. Overall, the mean age at the time of referral was 31.5 ± 6.9 years. The referral rates post‐NNP were higher among those without prior exposure to chemotherapy/radiation (0.33 pre‐NNP vs. 2.75 post‐NNP per 30 days, p < 0.01) and lower among those with prior exposure to chemotherapy/radiation (1.26 pre‐NNP vs. 0.70 post‐NNP per 30 days, p < 0.01). Conclusions After the launch of a dedicated fertility preservation nurse navigation program at our institution, we observed a higher number of referrals for FP as well as greater use of FP overall. While not the only variable that changed during this period, this program has optimized patient care and clinical workflow at our institution and serves as a model for such improvement.